O-alkylated quercetins with selective acetylcholinesterase and β-secretase inhibitions from Melicope glabra leaves, and their flavonols profile by LC-ESI-Q-TOF/MS. (September 2021) - Baiseitova, Aizhamal; Shah, Abdul Bari; Kim, Jeong Yoon; Ban, Yeong Jun; Kim, Jeong Ho; Nafiah, Mohd Azlan; Park, Ki Hun
Graphical abstract: Highlights: Quercetin derivatives (1 -13 ) including the new (2 ) were isolated from M. glabra . O -Alkylated quercetins were selective inhibitory potential toward hAChE and BACE1. All compounds from M. glabra had a significant antioxidant potentials. LC-ESI-Q-TOF/MS disclosed inhibitors as main metabolite of M. glabra leave extract. Abstract: Intensive investigation of phytochemicals from edible Melicope glabra leaves provided a series of O -alkylated quercetins (1 –13 ). The quercetin 1 bearing prenyl and methyl motif showed potent inhibition to human acetylcholinesterase (hAChE) with mixed type I mode, while quercetin was inactive. The position of methyl group was also a critical factor to hAChE inhibition: 1 (4′- O -methyl, IC50  = 12.7 μM) vs 2 (3′- O -methyl, IC50  = 119 μM). Inhibitory potency was doubly confirmed with the binding affinity ( K SV ) based on fluorescence quenching. O -Methyl groups on quercetin were observed to influence β-secretase (BACE1) inhibition. Thus, O -methylated quercetins (4 –6 ) displayed potential inhibitions against BACE1 with IC50 values of 1.3, 4.1, and 14.1 μM, respectively. All compounds (3 –6 ) have noncompetitive mode to BACE1. Additionally, all quercetin derivatives (1 –13 ) had antioxidant potentials against different radical sources (ABTS, ORAC and FRAP). The UPLC-ESI-Q-TOF/MS indicated that the leaves part had promising metabolites towards hAChE and BACE1 inhibitions, which are the most predominant phytochemicals.